METHODOLOGICAL APPROACHES TO THE FINANCIAL SECURITY OF BUSINESS PROCESSES AT THE ENTERPRISE - PETRASHEVSKA, Angelina; KOLONTAI, Svitlana; SOKOLOVSKA, Valentyna; PROKOPOVA, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article deals with topical issues of the importance of financial support for business processes of enterprises of all forms of ownership. Ways of financing the enterprise and methods of financial support of its activities are defined.The characteristics are provided and the advantages and disadvantages of the self-financing method, which is implemented by means of the turnover of own financial resources in production, are provided, the advantage of which is the independence of the enterprise from any financial institutions, and the disadvantage is the lack of funds to cover the expenses of the enterprise; the crediting method, which involves receiving funds in debt for a certain set period with the subsequent payment of interest, which is set by the creditor, the main advantage of the method is the quick receipt of the required amount of funds and the possibility of gradual return of funds, the disadvantage is the payment of interest; insurance method, which involves the application of certain measures for the formation of insurance funds in the financial equivalent, the advantage of which is the prevention of large expenses in insurance cases.The concept of business processes at the enterprise is defined and it is shown that their presence is an integral component for enterprises of all branches of the state's infrastructure, which strive to achieve the efficiency of their production activities. It is emphasized that an important condition for achieving the success of business processes at the enterprise is their financial support.
Keywords: financial support; methods; business process; enterprise